USING DRAMA TECHNIQUES AS A COMMUNICATIVE APPROACH IN TEACHING ENGLISH AS A FOREIGN LANGUAGE TO FOREIGN LEARNERS IN THE CLASSROOM OF SECONDARY SCHOOLS - MIRZA, SANAA' SA'EED (Journal of Duhok University, 2020)
ABSTRACTUnfortunately, many of our students graduate from secondary schools with no English at a satisfying level, except a few simple phrases with lowering of self-esteem and confidence. These problems come from teachers’ little awareness that the aim of teaching English as a foreign language is shifted from grammatical teaching to communicative teaching, and this shift requires the use of modern methods of teaching involving the drama techniques to achieve this aim. The current theoretical research aims at highlighting the role of the drama techniques approach in teaching English integrating it with their traditional approaches of teaching. This study hypothesizes that teaching English through drama techniques approach can help teachers achieve better results, vitalize the classroom, motivate both teachers and students, and have more fun. The significance of this study is to inform the present and the future teachers of the secondary schools the benefits of the integration of drama techniques with other methods in the classroom.  The current study is divided into five sections. Section one presents an introduction to the drama, its definition and how its techniques have been used in the field of education. Section two presents the literature review about the using of drama techniques in teaching English. Section three presents a brief study of the general concept of the Communicative Approach and its activities.  Section four concentrates on the definition of drama techniques approach, its techniques and importance in teaching English. This section also presents some advices to teachers in introducing drama techniques, preparing for a play, and the actual performance. Section five presents a conclusion that using drama techniques in the classroom improve students’ speech, communication and presentation skills, build their confidence, develop their critical thinking, engage them in a creative problem- solving and decision, develop their physical and emotional skills and encourage teamwork and co-operation. Finally, this research ends with a list of references in addition to Arabic and Kurdish synopsis.